IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING REPORT TEXT THROUGH NUMBERED HEADS TOGETHER - Yunita Khairani; Zainuddin (Universitas Negeri Medan, 2012)
This study attempted to improve students’ achievement in writing report text through numbered heads together. This study was conducted by using classroom action research. The subject of the research was class VIII/B at SMP SWASTA UPMI Medan that consisted of 32 students. The research was conducted in two cycles and the first cycle consisted of four meetings and the second cycle consisted of two meetings. The instrument for collecting quantitative data was a writing test and the instrument for collecting quantitative data included diary notes, observation sheets, interview and questionnaire sheets. Based on the writing test score, students’ score kept improving in every test. In test I, the mean was 66,4375, in test II the mean was 78,125 and in test III the mean was 87,5625. Based on the observation sheets and questionnaire sheets, it was found that the teaching learning process ran well. Students were active and interested in writing. The result of the research showed that Number Heads Together (NHT) significantly improved students’ achievement in writing report text. Key Words: Writing, Report, Number Heads Together.